If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = 2x + a Reorder the terms: Y = a + 2x Solving Y = a + 2x Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = a + 2x
| (9a-3)/3 | | Bj+m=j | | 16[x-3]=-80 | | 3d+2=12 | | X*.0147=(X-67) | | 11=3u-13 | | 11=3u+13 | | (x-67)=x*1.47 | | 6d+(5.5)=2d-(6.5) | | 6d+5.5=2d-(6.5) | | 6d+5.5=2d-6.5 | | 17x+3=17x | | -33*1/5 | | 288/6 | | (3/4)-(9/12) | | 68(x-3)=-2x+35.6 | | 10x+5y+15z= | | (x-1)(x+5)-(x+2)(x-3)=3(1+5x) | | -8x-18=6 | | (3/4)-(3/12)= | | y-21=2(x-9) | | m-8-2=4 | | TanX=27/32 | | 3/4-3/12 | | 5(3x-1)+7=2-(5x-3) | | F(x)=4x^2+7x-6 | | 5(2x+1)=3x+19 | | -7x^2+34x+5= | | x+2(80-x)=100-4(25-x) | | 6x/(x^2) | | g^2+4g-32=9 | | 5x=6x-14+12 |